Dynamic Gastrointestinal Digestion of Bovine, Caprine and Ovine Milk Reconstituted from Commercial Whole Milk Powders - Li S; Ye A; Cui J; Zhang Y; Ware L; Miller JC; Abbotts-Holmes H; Roy NC; Singh H; McNabb W (MDPI AG, 2024)
The global dairy market has been increasingly diversified with more dairy product offerings of milk products from different animal species. Meanwhile, milk powders remain the main exported dairy product format due to their ease of transportation. In this work, we studied the structural changes, protein hydrolysis and nutrient delivery during dynamic gastric digestion and small intestinal digestion of cow, goat and sheep milk reconstituted from commercial whole milk powders. The results show that the reconstituted milks digest similarly to processed fresh milk. The digestion behaviors of the three reconstituted ruminant milks are broadly similar (gastric coagulation, kinetics of gastric emptying of protein and fat and the high digestibility in the small intestine) with some differences, which are likely contributed by the processing history of the milk powders. The delivery of individual amino acids to the small intestine differed between the early and late stages of gastric digestion, which were primarily affected by the abundance of amino acids in caseins and whey proteins but also by the difference between milk types associated with their gastric coagulation behaviors. This work showed that powdered milk is similar to fresh processed milk in digestion behavior, and the inherent differences between ruminant milks can be modified by processing treatments.
Keywords: amino acids; cow milk; digestibility; goat milk; in vitro digestion; milk powder; sheep milk